The ethical contribution of organizations to society - Schwartz, Michael (College teacher); Harris, Howard (Head of Management Research); Comer, Debra R., 1960- (Research in ethical issues in organizations, 2015)
Organizations promote all sorts of activities. Indeed it is difficult to think of any activity today that is not reliant on an organization. This volume of Research in ethical issues in organizations contains two kinds of papers. First, papers that discuss what an organization provides to society, whether it be fast food, hypermarkets, education, training, supply chains or hamburgers, and an explanation of the ethical aspects of that particular contribution. Second, the ethics of the consumer's response in society to what an organization provides, be that the buying or boycotting of products, social approval or social condemnation.